Financing social ventures by crowdfunding: The influence of entrepreneurs’ personality traits - Bernardino, Susana (2018)
Studies on the profile of the social entrepreneurs that use crowdfunding (CF) for financing social projects are relatively rare, specifically in the context of Social Stock Exchange platforms. This research aims to understand the role played by social entrepreneurs’ personality traits on the choice between the traditional donation model and social CF to finance social projects. The particular case of the Portuguese Social Stock Exchange (PSSE) is presented and a quantitative and exploratory approach is used. The data were collected through a questionnaire that was emailed to non-governmental organizations in Portugal and founders of the projects listed on PSSE. Logistic regression is employed to predict the probability that a social entrepreneur would use PSSE rather than traditional financing. The predictor variables are based on the Big Five personality traits. Our investigation reveals that the conscientiousness personality trait is the only factor that might explain the use of the PSSE platform.